Preparation and Evaluation of a Molecularly Imprinted Sol-Gel Hybrid Material for Selective Solid-Phase Extraction of Sarafloxacin in Milk - Zhang, Dong; Lv, Yun-Kai; Chen, Rong; Shi, Chen-Chen (Asian Journal of Chemistry, 2013)
A new molecularly imprinted organic-inorganic hybrid material was prepared by sol-gel process in aqueous phase system based on the interaction of ion pair and hydrophobic between the sarafloxacin and the functional monomer. Sarafloxacin was used as the template molecular, 3-aminopropyltriethoxysilane as functional monomer and methyltrimethoxysilane as cross-linking agent. Synthesis and adsorption conditions were optimized for obtaining sorbent with the high adsorption capacity, selectivity, hardness and toughness. Binding study demonstrated that the imprinted hybrid composites showed excellent affinity and high selectivity to sarafloxacin. The present imprinted sorbent was successfully applied for the solid-phase extraction of fluoroquinolone antibiotics in milk. The mean recoveries of sarafloxacin and lomefloxacin in milk were 75.6-94.2 % and 61.73-88.56 %, respectively, with relative standard deviations (RSDs) of 3.56-5.21 %. The limits of detection (LOD, S/N = 3) and the limits of quantitation (LOQ, S/N = 10) of the proposed method were 0.010 and 0.0333 mg kg-1 for sarafloxacin hydrochloride, 0.012 and 0.04 mg kg-1 for lomefloxacin hydrochloride, respectively.